Self-Powered Transparent Stretchable 3D Motion Sensor - H. Guo; X. Chen; Miao, L; Wang, H; J Wan; H. Zhang (2019 20th International Conference on Solid-State Sensors, Actuators and Microsystems Eurosensors XXXIII (TRANSDUCERS EUROSENSORS XXXIII), 2019)
This paper reports a novel self-powered three-dimension motion sensor capable of independently detecting contact trajectory, pressure and velocity based on triboelectrification and electrostatic induction synchronously. Motion trajectories in the full plane can be identified by using a unique net-cross electrodes configuration design. In addition, the patterned silver nanowires (AgNWs) electrodes are sprayed onto the polydimethylsilane (PDMS) substrate to achieve good transparency and stretchability. By attaching the 3D motion sensor on human skin or robot surface directly, the 3D motion information of the object could be acquired including pressure, velocity and trajectory. The self-powered 3D motion sensor is a promising candidate in terms of human-computer interaction, anti-counterfeiting signatures, etc.